Assessing the sentinel capacity of mollusks, seawater and sediments for monitoring antimicrobial resistance in the marine environment - Arriagada, Gabriel; Canales, Libertad; Flores, Fabián; Reyes, Nicolás; Maldonado, Ismael; Lapierre, Lisette; Galarce, Nicolás (Frontiers in Veterinary Science, 2025)
IntroductionAlthough it is widely recognized that aquaculture activity is particularly relevant to the development and spread of AMR in the aquatic environment, national action plans against AMR typically do not include the marine environment among the compartments targeted for AMR monitoring and surveillance. This study aimed to compare the sentinel capacity of mollusks, seawater, and sediments for AMR surveillance in the marine environment of the Los Lagos region, Chile, using Escherichia coli as indicator bacteria and florfenicol, oxytetracycline, oxolinic acid, and flumequine as target antimicrobials.Methods101 mollusk, 76 seawater and 76 sediment samples were collected simultaneously from 76 sites in the coastal area of the Los Lagos region, Chile, between 2023 and 2024. All samples were subjected to conventional laboratory procedures for E. coli isolation. Minimum inhibitory concentrations (MICs) for florfenicol, oxytetracycline, oxolinic acid, and flumequine were estimated for each E. coli isolate, which was then classified as either “wild-type” (WT; i.e., susceptible) or “non-wild-type” (NWT; i.e., tolerant) based on local epidemiological cutoff values (COwt) calculated from the MIC results. The frequency of NWT E. coli isolates was calculated for each of the three compartments; significant differences in the probabilities of isolating E. coli and detecting NWT E. coli were assessed using logistic regression models.ResultsE. coli was isolated in 82.2% of the mollusk, 93.4% of the seawater, and 38.7% of the sediment samples. The COwt values were estimated in 32 μg/mL for florfenicol, 64 μg/mL for oxytetracycline, 1 μg/mL for oxolinic acid, and 2 μg/mL for flumequine. The proportion of NWT E. coli among the four antimicrobials was consistently higher in seawater (25.0% on average), followed by sediments (10.8%) and then mollusks (5.4%). Logistic models indicated that the probabilities of isolating E. coli and detecting NWT E. coli for the four antimicrobials studied significantly depend on the environmental compartment, with seawater having the highest probability. These results should be considered by authorities developing plans to monitor AMR in the marine environment.